2006
DOI: 10.1210/me.2005-0321
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of the Tumor Suppressor Gene Retinoic Acid Receptor β2 through the Phosphoinositide 3-Kinase/Akt Signaling Pathway

Abstract: The retinoic acid receptor beta2 (RARbeta2) is a potent, retinoid-inducible tumor suppressor gene, which is a critical molecular relay for retinoid actions in cells. Its down-regulation, or loss of expression, leads to resistance of cancer cells to retinoid treatment. Up to now, no primary mechanism underlying the repression of the RARbeta2 gene expression, hence affecting cellular retinoid sensitivity, has been identified. Here, we demonstrate that the phosphoinositide 3-kinase/Akt signaling pathway affects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…Finally, PGE 2 did not suppress the enhanced growth-inhibitory and apoptosis-inducing effects of the ATRA and celecoxib combination. Meanwhile, a study reported by Bruno Lefebvre proved that the phosphoinositide 3-kinase/Akt signaling pathway caused an increased tethering of the corepressor silencing mediator for retinoic and thyroid hormone receptors (SMRT) to the RARβ promoter, down-regulated the RARβ expression, and impaired cellular differentiation in response to the retinoid in P19 and HeLa Cells [26]. A study conducted by Schroeder discovered that even 5 µM of celecoxib could reduce phosphorylation levels of Akt and its direct downstream substrate GSK-3β in lung cancer cell lines, and the effects were augmented by a combination of celecoxib and 4HPR [12].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PGE 2 did not suppress the enhanced growth-inhibitory and apoptosis-inducing effects of the ATRA and celecoxib combination. Meanwhile, a study reported by Bruno Lefebvre proved that the phosphoinositide 3-kinase/Akt signaling pathway caused an increased tethering of the corepressor silencing mediator for retinoic and thyroid hormone receptors (SMRT) to the RARβ promoter, down-regulated the RARβ expression, and impaired cellular differentiation in response to the retinoid in P19 and HeLa Cells [26]. A study conducted by Schroeder discovered that even 5 µM of celecoxib could reduce phosphorylation levels of Akt and its direct downstream substrate GSK-3β in lung cancer cell lines, and the effects were augmented by a combination of celecoxib and 4HPR [12].…”
Section: Discussionmentioning
confidence: 99%
“…pSG5-hRAR, pSG5-hRXR, pSG5-hRXR, pSG5-hRXR, pSG5-hPPARγ (DR5)3-tk Luc, VP16-hRAR (PPRE)6-tk Luc, and Gal4-tk Luc were described elsewhere (58)(59)(60)(61) The pCMV-based human UCH-L1, USP22, and WWP2 expression vectors were purchased from OriGene.…”
Section: Methodsmentioning
confidence: 99%
“…Early studies showed that loss of RAR-β 2 expression in some forms of cancer (e.g., NSCLC) resulted from chromosome 3p deletion [62]), but in others (e.g., head and neck cancer) neither homozygous deletions nor gene rearrangements have been found [34]. Since those findings were published, other studies have shown that transcriptional deregulation can silence RAR-β 2 expression through decreased levels of co-activators, the presence of corepressors, or epigenetic mechanisms such as histone deacetylation [63][64][65][66][67][68]. Expression of RAR-β 2 also depends on the cellular level of retinoids because this receptor is itself an RAinducible gene.…”
Section: Molecular Mechanisms Responsible For Loss Of Rar-β 2 Expressionmentioning
confidence: 99%